PEDAGOGICAL BASIS OF DEVELOPING OF EDUCATIONAL WEB RESOURCE IN THE DISCIPLINE "INFORMATICS AND SYSTEMOLOGY" FOR FUTURE ECOLOGIES - Sherman M.; Stepanenko N.; Felbush A. (Kherson State University, 2017)
Based on the analysis of the information presented in psychological and pedagogical sources, educational and methodological works and the results of own research, a number of contradictions are identified, without which the process of formation of the professional information culture of future ecologists is problematic and uncertain. The main contradictions between the modern social requirements to the level of professional information and technological training of future ecologists and the current state of its organization in state agricultural universities are insufficient in the content of the disciplines «Fundamentals of Informatics and Computer Technology», «Informatics and Systemology», «Information Technologies», «Statistics» the direction needs by which the training of future ecologists is carried out; the actual realization of these disciplines is only a general development function in teaching process, while the realization of tasks of professional computer-information training of future ecologists is secondary task; the interdisciplinary and inter-cycle connections between professionally oriented ecological disciplines and computer science and related disciplines are insufficiently clearly identified and outlined. In order to overcome the above contradictions, we selected the professional-pedagogical principles of creating the content of the discipline «Informatics and Systemology» (principles of professional orientation, professional conformity, integrity, continuity, consistency, logical consistency, pedagogical expediency, information security ensuring, the starting level of mastering by means of information-communication technologies), there is structurization of content of discipline in accordance with the spatio- temporal boundaries, provided by the curriculum of future ecologists professional training, the components of methodological support of teaching of the discipline are developed. The web-resource of educational destination «Informatics and Systemology» was developed and approved, aimed at solving the tasks of computer-information training of future ecologists, containing information of knowledge (expert module), information about the student (student module), information about learning strategies (training module). The description of the functional and modes of using the author's web resource is presented.